The Effect of Teaching Assistance on The Hard Skills and Soft Skills of Accounting Education Students - Sriyani Mentari; Dudung Ma’ruf Nuris (The Future of Education Journal, 2024)
This research aims to determine whether implementing the independent learning program through the teaching assistance program can influence the soft and hard skills of accounting education students. Teaching assistance is the Independent Campus Learning program launched by the government. Teaching assistance aims to improve the competency of college graduate students in terms of soft and hard skills. Based on the initial observations of accounting education students at the Universitas Negeri Malang, various problems were found related to students' soft and hard skills in teaching assistance. This research uses quantitative methods by collecting data through questionnaires to measure teaching assistance on students' soft and hard skills. The research sample comprised 153 students in the accounting skills program at SMKN 12 Malang. Data analysis uses simple linear regression analysis to test the effect of teaching assistance on students' soft and hard skills. The research results show that teaching assistance can positively impact students' hard and soft skills. The conclusion of this research shows that teaching assistance is a program that can help students hone soft and hard skills to prepare themselves to become teachers in the real world. The experience students gain through teaching assistance can equip them to be ready for the world of work and to face real situations and conditions in the classroom.